Altered visual processing in the mdx52 mouse model of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Liber, André Maurício Passos; Joachimsthaler, Anneka; Saoudi, Amel; Goyenvalle, Aurélie; Rendon, Alvaro; Roger, Jérome E.; Ventura, Dora Fix; Kremers, Jan; Vaillend, Cyrille (Neurobiology of Disease, 2021)
The mdx52 mouse model of Duchenne muscular dystrophy (DMD) is lacking exon 52 of the DMD gene that is located in a hotspot mutation region causing cognitive deficits and retinal anomalies in DMD patients. This deletion leads to the loss of the dystrophin proteins, Dp427, Dp260 and Dp140, while Dp71 is preserved. The flash electroretinogram (ERG) in mdx52 mice was previously characterized by delayed dark-adapted b-waves. A detailed description of functional ERG changes and visual performances in mdx52 mice is, however, lacking. Here an extensive full-field ERG repertoire was applied in mdx52 mice and WT littermates to analyze retinal physiology in scotopic, mesopic and photopic conditions in response to flash, sawtooth and/or sinusoidal stimuli. Behavioral contrast sensitivity was assessed using quantitative optomotor response (OMR) to sinusoidally modulated luminance gratings at 100% or 50% contrast. The mdx52 mice exhibited reduced amplitudes and delayed implicit times in dark-adapted ERG flash responses, particularly in their b-wave and oscillatory potentials, and diminished amplitudes of light-adapted flash ERGs. ERG responses to sawtooth stimuli were also diminished and delayed for both mesopic and photopic conditions in mdx52 mice and the first harmonic amplitudes to photopic sine-wave stimuli were smaller at all temporal frequencies. OMR indices were comparable between genotypes at 100% contrast but significantly reduced in mdx52 mice at 50% contrast. The complex ERG alterations and disturbed contrast vision in mdx52 mice include features observed in DMD patients and suggest altered photoreceptor-to-bipolar cell transmission possibly affecting contrast sensitivity. The mdx52 mouse is a relevant model to appraise the roles of retinal dystrophins and for preclinical studies related to DMD.
CRIS-Team Scopus Importer:2021-02-26
Keywords: B-wave; Dp140; Dp260; Dp427; Duchenne muscular dystrophy; Dystrophin; Electroretinogram; Mouse model; Photoreceptors; Retina